The sequel eaudiobook A novel. - Korelitz, Jean Hanff (The Book Series, 2024)
"Fans of The Plot , and they were legion, will rejoice at this sequel, performed with mesmerizing skill by the wonderful Julia Whelan...Whelan's achievement here seems like a little miracle, relentlessly compelling and wonderfully satisfying."— AudioFile (Earphones Award Winner) After the "insanely readable" (Stephen King) and "perfectly told" (Malcolm Gladwell) New York Times bestseller The Plot comes Jean Hanff Korelitz's equally captivating new novel: The Sequel . Anna Williams-Bonner has taken care of business. That is to say, she's taken care of her husband, bestselling novelist Jacob Finch Bonner, and laid to rest those anonymous accusations of plagiarism that so tormented him. Now she is living the contented life of a literary widow, enjoying her husband's royalty checks in perpetuity, but for the second time in her life, a work of fiction intercedes, and this time it's her own debut novel, The Afterword . After all, how hard can it really be to write a universally lauded bestseller? But when Anna publishes her book and indulges in her own literary acclaim, she begins to receive excerpts of a novel she never expected to see again, a novel that should no longer exist. That it does means something has gone very wrong, and someone out there knows far too much: about her late brother, her late husband, and—just possibly—Anna, herself. What does this person want and what are they prepared to do? She has come too far, and worked too hard, to lose what she values most: the sole and uncontested right to her own story. And she is, by any standard, a master storyteller. With her signature wit and sardonic humor, Jean Hanff Korelitz gives listeners an antihero to root for while illuminating and satirizing the world of publishing in this deliciously fun and suspenseful read. A Macmillan Audio production from Celadon Books.